Inverse association of a traditional Korean diet composed of a multigrain rice-containing meal with fruits and nuts with metabolic syndrome risk: The KoGES - Kim, Min Jung; Hur, Haeng Jeon; Jang, Dai Ja; Kim, Myung-Sunny; Park, Sunmin; Yang, Hye Jeong (Frontiers in Nutrition, 2022)
Background: Hansik, a traditional Korean diet, may have a beneficial impact on metabolic syndrome(MetS) potentially due to increasing MetS prevalence after dietary westernization. We examined the hypothesis that adherence to the hansik diet may be inversely associated with the risk of MetS and its components and sought to understand the gender differences in 58,701 men and women aged over 40. Materials and methods: Hansik was defined using 14 questionnaires from which the Korean dietary pattern index(Kdiet-index) was generated by summing their scores. Low-hansik intake was defined as the Kdiet-index with < 8. MetS was categorized based on the 2005 revised NCEP-ATP III criteria modified for Asians. Results: An analysis of the 14 components of the Kdiet-index showed that the high intake of a meal with rice, fruits, and their products, and nuts, and low intake of fried foods were inversely associated with MetS by 0.707, 0.864, 0.769, and 0.918 times, respectively. More women and more educated and lower-income participants belonged to the high-hansik group. Participants with high self-rated health scores consumed more hansik. All participants on a high-hansik diet were associated with 0.87 times lower risk of MetS. Specifically, women on a high-hansik diet were associated with 0.88 times lower risk of MetS. Body composition, including the body mass index, waist circumference, and fat mass, was inversely associated with hansik intake, and the skeletal muscle mass index was positively associated with the hansik intake in each gender and all participants. In all the participants in the high-hansik group, no significant changes were seen in the serum glucose and lipid parameters. However, a high-hansik intake improved the serum high-density lipoprotein cholesterol concentrations. Regardless of gender, all participants in the high-hansik group had a lower glomerular filtration rate. Conclusions: Hansik, a meal containing rice with fruits and nuts, was inversely associated with MetS risk, with its primary effects on body fat and increased muscle mass.